Neuromechanobiology: An Expanding Field Driven by the Force of Greater Focus. Issue 19 (2nd August 2021) - Motz, Cara T.; Kabat, Victoria; Saxena, Tarun; Bellamkonda, Ravi V.; Zhu, Cheng
Abstract: The brain processes information by transmitting signals through highly connected and dynamic networks of neurons. Neurons use specific cellular structures, including axons, dendrites and synapses, and specific molecules, including cell adhesion molecules, ion channels and chemical receptors to form, maintain and communicate among cells in the networks. These cellular and molecular processes take place in environments rich of mechanical cues, thus offering ample opportunities for mechanical regulation of neural development and function. Recent studies have suggested the importance of mechanical cues and their potential regulatory roles in the development and maintenance of these neuronal structures. Also suggested are the importance of mechanical cues and their potential regulatory roles in the interaction and function of molecules mediating the interneuronal communications. In this review, the current understanding is integrated and promising future directions of neuromechanobiology are suggested at the cellular and molecular levels. Several neuronal processes where mechanics likely plays a role are examined and how forces affect ligand binding, conformational change, and signal induction of molecules key to these neuronal processes are indicated, especially at the synapse. The disease relevance of neuromechanobiology as well as therapies and engineering solutions to neurological disorders stemmed from this emergent field of study are also discussed. Abstract : Increasing evidence shows mechanics affects neural development and function. This review of the emerging field of neuromechanobiology focuses on the effects of forces on neurons at the molecular level and relates forces to neurological diseases, biomaterials‐based therapies, and clinical application.